Rapid separation of very low concentrations of bacteria from blood - Buchanan, Clara M. (2017)
A rapid and accurate diagnosis of the species and antibiotic resistance of bacteria in septic blood is vital to increase survival rates of patients with bloodstream infections, particularly those with carbapenem-resistant enterobacteriaceae (CRE) infections. The extremely low levels in blood (1 to 100 CFU/ml) make rapid diagnosis difficult. In this study, very low concentrations of bacteria (6 to 200 CFU/ml) were separated from 7 ml of whole blood using rapid sedimentation in a spinning hollow disk that separated plasma from red and white cells, leaving most of the bacteria suspended in the plasma. Following less than a minute of spinning, the disk was slowed, the plasma was recovered, and the bacteria were isolated by vacuum filtration. The filters were grown on nutrient plates to determine the number of bacteria recovered from the blood. Experiments were done without red blood cell (RBC) lysis and with RBC lysis in the recovered plasma. While there was scatter in the data from blood with low bacterial concentrations, the mean average recovery was 69%. The gender of the blood donor made no statistical difference in bacterial recovery. These results show that this rapid technique recovers a significant amount of bacteria from blood containing clinically relevant low levels of bacteria, producing the bacteria in minutes. These bacteria could subsequently be identified by molecular techniques to quickly identify the infectious organism and its resistance profile, thus greatly reducing the time needed to correctly diagnose and treat a blood infection.